Knowledge and performance of pregnant women referring to Shabihkhani hospital on exercises during pregnancy and postpartum periods - Masoumeh Abedzadeh (فصلنامه دانشگاه علوم پزشکی جهرم, 2011)
Introduction: Physical activity plays an important role in the health of pregnant women. This study is aimed to determine the knowledge and performance of pregnant women on exercises during pregnancy and postpartum periods. Material and Methods:In this descriptive-analytic study, 200 women were assessed. Data including demographic characteristics and knowledge and performance of women about pregnancy and postpartum exercises were recorded through a questionnaire and analyzed with χ2 statistical test and then odds ratio (OR) and 95% confidence Interval (CI) were estimated.Results:The mean (±SD) knowledge score was 21.6±7.7. 60% of the women had moderate knowledge about pregnancy and postpartum exercises. Only 19% of the cases were recommended to perform exercise and in 68.4% of them it was done by a midwife. During pregnancy, only 39% of the women had physical activity and most of the exercise was walking. 48.7% of the women had continued to exercise till the 9th month of pregnancy. There was a significant difference between the participants' knowledge and physical activity during pregnancy (P=0.025) but there was no correlation with other variables. Conclusion:Most of the women had moderate knowledge about physical activities and did not have a good performance. Therefore, we emphasize educating women about the importance of exercise and its role in improving the women's performance during pregnancy.